Peran Tenaga Kesehatan dalam Perilaku Imunisasi Dasar pada Peserta Didik PAUD Kelurahan Ciampea dan Kalibata - Izza Suraya; Hidayati Hidayati; Rizka Ariesta Putranti; Apriyanto Apriyanto; Julia Julia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Immunization is effective way to reduce morbidity and mortality of infectious diseases. However, there is only 59,2% early child in Indonesia is fully immunized. Health workers have an important role in that practice. Immunization status of children in Ciampea and Kalibata Early Childhood School has not known Their health worker’s role either. Therefore, this study was conducted to know the role of health worker in early childhood students in Ciampea and Kalibata Preschool. This study used a cross-sectional design. With quota as its sampling technique, there were 145 early child aged 12-59 months. multivariate. After multivariate analysis, the result of this study describes there is health worker advice is significantly associated with primary immunization with AOR 5,27 (95%CI: 1,05 – 26,32) dan p-value = 0,043. The mother who had to advise from health workers is 5,27 likely had fully immunized their children. Hence, health workers capacity should be increased to get more fully immunized early child.